Pura Luhur Tamba Waras: aspects of sustainable tourism and spiritual tourism - I Made Rony Mulia Kusuma Putra; I Gede Mudana; I Made Darma Oka; Muhamad Nova (Politeknik Negeri Bali, 2022)
This research aims to analyze the implementation of sustainable tourism in spiritual tourism at Pura Luhur Tamba Waras in Desa Sangketan, Tabanan Regency, Bali, Indonesia. This research uses qualitative analysis techniques. The data source used is secondary data and is accessed through company documents, journals, books, articles, and websites. The results show that sustainable tourism in spiritual tourism at Pura Luhur Tamba Waras are the application of basic concepts in sustainable tourism, namely the social concept of cooperation. The economic concept has also been implemented very well, namely the surrounding community can sell spiritual facilities and infrastructure in the temple area, but the implementation of the environmental concept is not good because the waste that is used for spiritual tourism is not well managed. Pura Luhur Tamba Waras has implemented three basic concepts of sustainable tourism, namely social, economic and environmental but the concept of the environment has not been maximally implemented.